Analysis of Risk Factors for Stunting in Toddlers - Donal Nababan; Hadiah Kurnia Putri (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2026)
Stunting has been a significant public health burden in Indonesia, reflecting chronic malnutrition during the critical first 1,000 days of life. Despite a national decline, local prevalence in rural areas, such as in Langkat District, remains a challenge.  This study aims to analyze interrelated risk factors: maternal knowledge, antenatal care (ANC) visits, iron supplementation, exclusive breastfeeding, and complementary feeding, that contribute to stunting in toddlers. A cross-sectional study was conducted in the working area of the Secanggang Community Health Center, Langkat. A total of 162 toddlers participated in this study. Data were collected through interviews with mothers and anthropometric measurements. Bivariate analysis was performed using the Chi-square test to determine the relationship between variables. The prevalence of stunting was 40.7% (n=66). Statistical analysis showed that all factors studied were significantly associated with stunting (p < 0.05). Mothers' knowledge about stunting was generally low (70.4%). The highest risk was found in infants who did not receive exclusive breastfeeding, where 25.9% experienced stunting compared to those who received exclusive breastfeeding. Inadequate ANC visits (p < 0.05) and poor adherence to iron (Fe) tablets (p < 0.05) also significantly increased the risk of growth failure. Stunting in this population is triggered by the interaction between low maternal literacy and suboptimal antenatal and postnatal care. These findings indicate an urgent need for maternal education programs and breastfeeding support integrated into the primary health care (Puskesmas) framework to reduce long-term growth disorders. Keywords:  Maternal Knowledge, Antenatal Care, Exclusive Breastfeeding, Stunting, Toddlers